2023
DOI: 10.14309/ajg.0000000000002619
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Natural History of Autoimmune Gastritis: Results From a Prospective Monocentric Series

Emanuela Miceli,
Marco Vincenzo Lenti,
Antonella Gentile
et al.

Abstract: Objectives: The natural history of autoimmune gastritis (AIG) has been poorly described. We herein report the long-term natural history and clinical clustering of the full spectrum of AIG, from the potential to the complicated stage. Methods: Prospective, single-center study conducted in a tertiary referral center. AIG patients at any stage (0=potential; 1=early; 2=florid; 3=severe; 4=complicated) were enrolled (January 2000-December 2022). The histopat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(1 citation statement)
references
References 34 publications
0
1
0
Order By: Relevance
“…Rugge et al [16] concluded that in patients in whom previous or current Hp infection has been definitively ruled out (through serology, histology and molecular tests), the corpus-restricted inflammation and atrophy characteristic of AAG does not result in a significant increase in the risk of GC. In contrast, other recent prospective studies reported an increased incidence of GC and high-grade dysplasia in a long-term follow-up in Hp-negative patients with AAG [111,112]. Methodological issues and different study populations, such as studies being limited to PA or lacking exclusion of Hp infection or inclusion of patients at a pre-atrophic stage, are probably responsible for the different GC risk estimates in AAG [45,113].…”
Section: Aag and Hypochlorhydria: Is There An Increased Risk Of Gastr...mentioning
confidence: 88%
“…Rugge et al [16] concluded that in patients in whom previous or current Hp infection has been definitively ruled out (through serology, histology and molecular tests), the corpus-restricted inflammation and atrophy characteristic of AAG does not result in a significant increase in the risk of GC. In contrast, other recent prospective studies reported an increased incidence of GC and high-grade dysplasia in a long-term follow-up in Hp-negative patients with AAG [111,112]. Methodological issues and different study populations, such as studies being limited to PA or lacking exclusion of Hp infection or inclusion of patients at a pre-atrophic stage, are probably responsible for the different GC risk estimates in AAG [45,113].…”
Section: Aag and Hypochlorhydria: Is There An Increased Risk Of Gastr...mentioning
confidence: 88%